Research Model of Fiqh - Nadifah Nadifah; Rina Firgiawan; M Taupik; Wahyu Hidayat; Anggi Afrina Rambe (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2025)
Fiqh or Islamic law is one of the most well-known fields of Islamic study among the general public. This is partly because fiqh is directly related to people's lives. From birth to death, humans are always connected to fiqh. For example, who is responsible for providing for them, who their parents are, and even when they are buried, these matters are related to fiqh. Due to its nature and function, fiqh is categorized as al-hal science, which is the science related to human behavior, and is considered a mandatory science to study, because with this knowledge, a person can fulfill their obligation to serve Allah through worship such as prayer, fasting, hajj, and so on. Furthermore, if legal science or fiqh is called idealistic, it does not mean that these legal materials themselves do not have practical considerations related to the needs of society. Islamic legal philosophy is essentially nothing more than the development and analysis of abstract Sharia law, not positive law that originates from and is sourced from court forums. Therefore, the characteristic that defines Islamic law in the sense of law that governs the lives of Muslims is the distinction between ideal teachings and factual practices, between Sharia as taught by classical legal scholars on the one hand and positive law as applied in courts on the other.